Pathotypes and probiotics: response to a commentary on the detection of a Shiga toxin producing Escherichia coli in a Crohn’s disease patient - Rodrigues, Josias [UNESP] (Biomed Central Ltd, 2015)
A recent report on the detection in a Crohn's disease (CD) patient of an adherent and invasive Shiga toxin producing Escherichia coli (STEC) (Gut pathogens 2015, 7:2) prompted a commentary expressing some skepticism on the significance of the paper findings (Gut pathogens 2015, 7:15). Besides focusing on recurrent issues concerning the difficulties in defining a pathogen, the opinion considers recent data demonstrating the presence of virulence factors in a commercial probiotic. In response to the commentary's observations, additional information on the described STEC strain, as well as a short discussion on CD associated E. coli are presented here.